1998
DOI: 10.1159/000029813
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Human Skin Barrier Modulation by Topical Application of Fatty Acids

Abstract: The in vivo effects of fatty acids on skin barrier function were assessed by measuring: (i) transepidermal water loss (TEWL), (ii) diffusion lag times for hexyl nicotinate (HN), and (iii) irritant skin response using laser Doppler velocimetry (LDV) in combination with visual scoring. Two classes of fatty acids have been investigated: straight-chain saturated fatty acids (SFA), having 6–12 carbon atoms, and unsaturated fatty acids (UFA): oleic, linoleic, α-linolenic and arachidonic acids. It has been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 30 publications
4
27
0
2
Order By: Relevance
“…The vehicle chosen for dosing of OA (propylene glycol 50%, ethanol 30%, and water 20%) was selected to minimize the potential for increasing Malassezia numbers (Faergemann, 2000). The lack of response of non-susceptible individuals is particularly noteworthy, in that another report (Tanojo et al, 1998) showed significant barrier disruption effects from a slightly higher dose of OA in a similar vehicle. Our result strongly supports that dandruff sufferers display an underlying difference in permeability barrier function, relative to non-dandruff individuals, that renders them more susceptible to fatty acid-induced barrier disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vehicle chosen for dosing of OA (propylene glycol 50%, ethanol 30%, and water 20%) was selected to minimize the potential for increasing Malassezia numbers (Faergemann, 2000). The lack of response of non-susceptible individuals is particularly noteworthy, in that another report (Tanojo et al, 1998) showed significant barrier disruption effects from a slightly higher dose of OA in a similar vehicle. Our result strongly supports that dandruff sufferers display an underlying difference in permeability barrier function, relative to non-dandruff individuals, that renders them more susceptible to fatty acid-induced barrier disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in order to preclude inadvertently increasing the number of Malassezia, the OA (a known Malassezia carbon source as well as metabolite) was dosed in an anti-microbial vehicle containing 50% propylene glycol (Faergemann and Fredriksson 1980;Faergemann, 2000). Propylene glycol has previously been used as a carrier for fatty acids used in human skin barrier studies (Tanojo et al, 1998).…”
mentioning
confidence: 99%
“…Potts et al [18] demonstrated that oleic acid (OA) can increase the skin water permeability, which may due to the formation of permeable interfacial defects and in turn creates a separate phase within SC lipids. Moreover, topical application of unsaturated fatty acid on human forearm was more effective in enhancing TEWL and more irritating than saturated fatty acid [19]. Choi et al [20] and Jiang et al [21] reported that repeated OA treatment on hairless mouse skin induced chronic skin barrier impairment, including increased TEWL, abnormalities of SC lipid bilayer, lacunar dilatation, as well as loss of epidermal basal layer's calcium gradient.…”
Section: Sebum and Skin Barriermentioning
confidence: 99%
“…Generally speaking, n-hexadecane, oleic acid and SDS are accepted skin barrier-disturbing agents known to cause irritation. 40 After pretreatment with DGC or WSC, each irritant was applied to hairless mouse skin (Tables 3-5). Because the purpose of this experiment was to compare protective skincare efficacy between DGC and WSC, a lower density (0.6wt%) of DGC and WSC was used compared with the above-mentioned test concentration (1.0wt%) aimed at curative skincare.…”
Section: Preventive Effect From Chemicals Disturbance Of Skin Barriermentioning
confidence: 99%